PROYEKSI INDEKS PEMBANGUNAN MANUSIA (IPM) KABUPATEN ALOR TAHUN 2030 MENGGUNAKAN PENERAPAN MODEL EKPONENSIAL DAN MODEL LOGISTIK - Melki Imamastri Puling Tang; Abraham Puling Tang (Fakultas Pertanian, Universitas Timor, 2021)
The population growth rate of Alor district continues to increase every year. To estimate the population for the following year, population estimates are usually used, which are used as the basis for economic and social planning to determine future needs. Population growth models with exponential and logistic models are well known in determining population growth. The research method used is a case study of the population in Alor Regency. The data in this study is population data obtained from the Central Statistics Agency (BPS) Alor from 2015-2019. The data that has been obtained is processed using Exponential and Logistics methods to obtain forecast data or projections of the population of Alor Regency in 2020 Alor. Based on the results of the discussion above, exponential and logistic models can be used to predict the population of Aor Regency in 2030. Based on the results of the above discussion, exponential and logistical models can be used to predict the number of Human Development Index of Alor Regency in 2030. Predicted number of Human Development Index of Alor Regency in 2030, based on the results of exponential model 1 is 64.12; exponential model 2 is 65.69; and the exponential model 3 is 65.72. Meanwhile, the prediction of the Human Development Index for Alor Regency in 2030 based on the logistics model is 64.98.